1975
DOI: 10.1002/zaac.19754120206
|View full text |Cite
|
Sign up to set email alerts
|

Zur Konstitution von Bis‐(phenanthrolin)‐kobalt(II)‐Komplexen

Abstract: IR‐ und elektronenspektroskopische Untersuchungen an [Co(phen)2X2]‐Komplexen (XF−, Cl−, Br−, J−, NCS−, NCO−, NO3−, SO 4−−, ClO4−, HCOO−, H3CCOO−, H5C2COO−, n‐H7C3COO− und Salicylat) wurden zur weiteren Charakterisierung dieses Koordinationstyps durchgeführt. Die Untersuchungsergebnisse deuten auf cis‐oktaedrische Ligandenanordnung in diesen Verbindungen hin. Aus den v1‐ und v3‐Übergängen der Elektronenspektren wurden die Ligandenfeldparameter B und Dq berechnet sowie die Lage des Zweielektronenübergangs v2 be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1975
1975
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Solvent-free Co-phen complexes with bidentate sulfate ligands (Palade et al, 1973;Hennig et al, 1975), with monodentate sulfate ligands (Li et al, 1987), and with bidentate bridging sulfate ligands (Palade et al, 1976) have been synthesized. The crystal structure of the title complex, (I), has not hitherto been reported.…”
Section: Commentmentioning
confidence: 99%
“…Solvent-free Co-phen complexes with bidentate sulfate ligands (Palade et al, 1973;Hennig et al, 1975), with monodentate sulfate ligands (Li et al, 1987), and with bidentate bridging sulfate ligands (Palade et al, 1976) have been synthesized. The crystal structure of the title complex, (I), has not hitherto been reported.…”
Section: Commentmentioning
confidence: 99%
“…For related cobalt compounds with monodentate, bidentatebridging sulfate ligands, see: Hennig et al (1975); Li & Zhou (1987); Song et al (2008); Zheng & Lin (2003). For related complexes with bidentate-chelating ligands, see: Lu et al (2006); Paul et al (2002); Wang et al (2009).…”
Section: Related Literaturementioning
confidence: 99%
“…Although many transtion metal complexes with sulfate ions as monodentate, bidentate and bidentate-bridging ligands have been structurally characterized (Hennig et al, 1975;Zheng & Lin, 2003;Song et al, 2008), as far as we know, the reports on complexes with bidentate-chelating sulfate ligands are few (Paul et al, 2002;Lu et al, 2006;Wang et al, 2009). Here, we report the crystal structure of the new complex [CoSO 4 (C 12 H 8 N 2 ) 2 ].C 3 H 8 O 2 unexpectedly obtained during an attempt to synthesize a mixed-ligand complex of cobalt with phen and melamine via a solvothermal reaction, which is analogue with a previously reported Co II complex (Zhong et al, 2006).…”
Section: Sup-1mentioning
confidence: 99%
“…For applications of cobalt complexes, see: Bottcher et al (1995). For related Co compounds with sulfate ions, see: Henning et al (1975); Lu et al (2006); Zheng & Lin (2003); Paul et al (2002). For isotypic structures, see: Zhong et al (2006).…”
Section: Related Literaturementioning
confidence: 99%
“…Since the first octahedral coordination cobalt complexes was recognized by Werner, some metal cobalt complexes as potent antiviral agents (Bottcher et al, 1995) have been previously reported. Furthermore, many cobalt complexes with monodentate sulfate ions (Henning et al, 1975;Lu et al, 2006), bidentate sulfate ions (Zheng & Lin, 2003) and bidentate bridging sulfate ions (Paul et al, 2002) have been synthesized and characterized. In our investigation, we have carried out solvothermal reactions using metal sulfate and mixed-ligands with the aim of obtaining complexes retainig some of the solvent molecules capable of hydrogen bonding.…”
Section: Tablementioning
confidence: 99%